Functional Programming in C++ - Cukic, Ivan (Manning Publications, 2019)
Functional Programming in C++ helps you unleash the functional side of your brain, as you gain a powerful new perspective on C++ coding. You'll discover dozens of examples, diagrams, and illustrations that break down the functional concepts you can apply in C++, including lazy evaluation, function objects and invokables, algebraic data types, and more. As you read, you'll match FP techniques with practical scenarios where they offer the most benefit.